The story of Prophet Hud - Khan,saniyasnain (china goodwordbooks, 2022)
The story of Prophet Hud, as told by Saniyasnain Khan, focuses on Hud's mission to guide the people of Ad towards worshipping Allah alone and abandoning idolatry. Despite Hud's warnings and pleas, the people of Ad, known for their strength and arrogance, rejected his message. Consequently, Allah sent a powerful, destructive wind that wiped out the disbelieving Ad, while Hud and his followers were saved